2014
DOI: 10.1049/iet-gtd.2013.0643
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sub‐synchronous resonance in doubly‐fed induction generator‐based wind farms interfaced with gate – controlled series capacitor

Abstract: This paper first presents a step-by-step tutorial on modal analysis of a doubly-fed induction generator (DFIG)-based series compensated wind farm. The model of the system includes a wind turbine aerodynamics, a sixth-order order induction generator, a second-order two-mass shaft system, a fourth-order order series compensated transmission line, an eighth-order rotor-side converter (RSC) and grid-side converter (GSC) controllers, and a first-order DC-link model. Then, using modal analysis and time-domain simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 29 publications
0
72
0
Order By: Relevance
“…The purpose of series compensation in transmission lines are to decrease the line equivalent inductance, and consequently to increase the system stability and maximum transferable power of the line [26]- [30]. Verification of the proposed fault location technique in the presence of series compensation demonstrates its universality and the fact that this method could also be applicable to the transmission networks.…”
Section: Lines Compensated With Capacitorsmentioning
confidence: 91%
“…The purpose of series compensation in transmission lines are to decrease the line equivalent inductance, and consequently to increase the system stability and maximum transferable power of the line [26]- [30]. Verification of the proposed fault location technique in the presence of series compensation demonstrates its universality and the fact that this method could also be applicable to the transmission networks.…”
Section: Lines Compensated With Capacitorsmentioning
confidence: 91%
“…In this case, the typical choices are the rotor speed, the current through the line and the voltage across the series capacitor. In [13,19] it is shown that the voltage across the capacitor has the best characteristics, but it requires a remote measurement that introduces a time delay in the control loop. An alternative to this signal is proposed in [13,17] where the voltage across the capacitor is calculated integrating the line current.…”
Section: Three-parameter Analysismentioning
confidence: 99%
“…A procedure to study SSI in wind farms was presented in [11] and a general methodology was proposed in [12]. Mitigation strategies using dedicated controllers were analyzed in [6,[13][14][15][16][17][18], and using Flexible AC Transmission Systems (FACTS) in [19][20][21]. SSO also appeared in a 150 MVA DFIG wind farm located in Minnesota, USA.…”
Section: Introductionmentioning
confidence: 99%
“…The controller of the ASPSH is composed of three separate parts including hydro pump turbine (HPT) controller, the RSC controller, and the GSC controller. The RSC and GSC controllers are similar to the DFIG-based wind turbine [1] in generating mode, while the HPT controller is an additional controller for the ASPSH, adjusting the rotor speed as well as contributing in the frequency control of the grid. However, the plant contributes in the grid frequency control via the RSC in the motor mode, and the HPT is controlled to optimize the HPT efficiency, as shown in Fig.…”
Section: Basic Structure Of the Pshmentioning
confidence: 99%
“…The DFIM uses a back-to-back converter, whose power rating is partial scale of the DFIM rated power, between the rotor and stator terminal that can transfer the mechanical power through both the stator and the rotor [1]. The transferred power through the rotor depends on the value of the rotor slip.…”
Section: Introductionmentioning
confidence: 99%